2016
DOI: 10.1111/psyp.12617
|View full text |Cite
|
Sign up to set email alerts
|

Decreased reaction time variability is associated with greater cardiovascular responses to acute stress

Abstract: Cardiovascular (CV) responses to mental stress are prospectively associated with poor CV outcomes. The association between CV responses to mental stress and reaction times (RTs) in aging individuals may be important but warrants further investigation. The present study assessed RTs to examine associations with CV responses to mental stress in healthy, older individuals using robust regression techniques. Participants were 262 men and women (mean age = 63.3 ± 5.5 years) from the Whitehall II cohort who complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Moreover, additional pairwise comparisons showed that the differences in HRV approached the conventional level of significance between baseline and recovery ( p = 0.07) and stressor to recovery ( p = 0.07). The reduction in HRV during a stressor is consistent with differences observed in other studies that have utilized a standard laboratory stressor (Arch et al, 2014; Wawrzyniak et al, 2016) and greater than reductions observed during personally relevant, stressful imagery task (Levine et al, 2016). Participants reported that they were able to easily generate their failure images ( M = 5.26 out of 7, SD = 1.24), and these images were clear ( M = 5.63 out of 7, SD = 1.17), emotional ( M = 4.60 out of 7, SD = 0.99) and meaningful ( M = 5.20 out of 7, SD = 1.10).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, additional pairwise comparisons showed that the differences in HRV approached the conventional level of significance between baseline and recovery ( p = 0.07) and stressor to recovery ( p = 0.07). The reduction in HRV during a stressor is consistent with differences observed in other studies that have utilized a standard laboratory stressor (Arch et al, 2014; Wawrzyniak et al, 2016) and greater than reductions observed during personally relevant, stressful imagery task (Levine et al, 2016). Participants reported that they were able to easily generate their failure images ( M = 5.26 out of 7, SD = 1.24), and these images were clear ( M = 5.63 out of 7, SD = 1.17), emotional ( M = 4.60 out of 7, SD = 0.99) and meaningful ( M = 5.20 out of 7, SD = 1.10).…”
Section: Resultssupporting
confidence: 88%
“…Indeed, the regulation of HRV has implications for well-being (Porges, 2007; Thayer et al, 2012), health (Thayer and Sternberg, 2006) and performance (Wawrzyniak et al, 2016; Williams et al, 2016) that may be beneficial to athletes. For example, sustained low or dysregulated HRV predicts behavioral risk factors (inhibition and risk aversion; Porges, 2007; Thayer et al, 2012) and psychological risk factors (negativity bias and poor emotional regulation; Thayer and Lane, 2009; Thayer et al, 2012) for psychopathology and adverse health (e.g., glucose dysregulation, inflammation and disrupted hypothalamic-pituitary axis function; Thayer and Sternberg, 2006; Thayer and Lane, 2009; Juster et al, 2010; Thayer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Stroop test will be administered over a 5 min period using a validated software package to provide a measure of reaction time, sensitivity to interference and the ability to suppress an automated response—reading colour names in favour of naming the font colour 53. To examine psychophysiological reactivity, acute stress will be induced using a 5 min mirror-tracing task (Campden Instruments), during which measures of blood pressure and heart rate will be taken 54…”
Section: Methods and Analysismentioning
confidence: 99%
“…The mean RT was calculated as the time between the presentation of the response signal (S2) and the subject's button press response. The coefficient of variation of the RT (CV-RT) was defined as the consistency of performance (Deary & Der, 2005; Kofler et al., 2013; Wawrzyniak, Hamer, Steptoe, & Endrighi, 2016). Trials in which the RT was less than 100 ms were defined as responses that were too fast (Lamme & Roelfsema, 2000; Swensson, 1988), and trials in which the RT was greater than 3 SD were defined as responses that were two slow (Miller, 1991); these too fast and too slow trials were excluded from the analysis of the RT and CV-RT.…”
Section: Methodsmentioning
confidence: 99%